2004
DOI: 10.1038/modpathol.3800078
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase (ALK 1) staining and molecular analysis in inflammatory myofibroblastic tumours of the bladder: a preliminary clinicopathological study of nine cases and review of the literature

Abstract: Inflammatory myofibroblastic tumours (IMFT) may arise at any anatomical site, including lung, soft tissues, retroperitoneum and bladder. Although morphologically similar, these lesions encompass a spectrum of entities with differing aetiology, ranging from reactive/regenerative proliferations to low-grade neoplasms with a risk of local recurrence, but no significant metastatic potential. Vesical IMFT usually presents as a polypoid mass with a pale firm cut surface and can be of considerable size, mimicking a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
2
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 20 publications
1
103
2
7
Order By: Relevance
“…23,24 Spindle cell carcinomas are negative for ALK-1 in the few cases examined. 24,25 We found only one of 12 (1/12) cases to be very focally positive for p63 and none for TTF-1 and MOC-31.…”
Section: Discussionmentioning
confidence: 71%
“…23,24 Spindle cell carcinomas are negative for ALK-1 in the few cases examined. 24,25 We found only one of 12 (1/12) cases to be very focally positive for p63 and none for TTF-1 and MOC-31.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to previous reports, in the present study, we noted ALK-1 expression in 62% (13 of 21 cases) of bladder inflammatory myofibroblastic tumor cases. 7,[13][14][15]19 ALK-1 positivity by immunohistochemistry was not detected in leiomyosarcoma or sarcomatoid carcinoma. Previous studies have also reported ALK expression in both alveolar and embryonal rhabdomyosarcoma, using a polyclonal ALK antibody.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 93%
“…Originally identified as a protein overexpressed in anaplastic large-cell lymphoma, ALK-1 has subsequently been shown to be overexpressed in a substantial proportion of inflammatory myofibroblastic tumors of various anatomic locations, [1][2][3][4][5][6][7][8][9]15 including the urinary bladder. 3,7,[10][11][12][13][14]16,19,25 Several studies have demonstrated a variable degree of cytoplasmic immunohistochemical staining for ALK-1. In inflammatory myofibroblastic tumor of the urinary bladder, positivity for ALK-1 by immunohistochemistry ranges from 33 to 89%, whereas ALK-1 protein expression in leiomyosarcoma and sarcomatoid urothelial carcinoma has not been reported, suggesting that ALK-1 immunohistochemical studies may be useful in the differentiation of inflammatory myofibroblastic tumor from other spindle cell lesions in the urinary bladder.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 99%
See 2 more Smart Citations